Career Development Programs and Employee Performance in Kanungu District, South Western Uganda - Ainebyona, Alex; Moses, Agaba (International Journal of Science Academic Research, 2022)
Kanungu District Local Government has been experiencing poor staff performance in all departments such as Finance, Production, Health, Management and Planning, among others which was manifested through staff turnover, poor quality work and ineffective service delivery. This state of affairs raised a lot of concern among politicians, staff and the communities who directly benefit from their services. It also negatively impacted on the performance of the town councils because of the time lag they take to mobilize resources to deliver services. Despite the training support advanced to employees in town councils, they have persistently registered poor performance. The objectives of the study were to establish the relationship between staff training and employee performance in Kanungu District Local government, to determine the relationship between career advancement and employee performance in Kanungu District Local government and to determine the relationship between career planning and employee performance in Kanungu District Local government. The study espoused a cross sectional research design. The study used a sample of 164 respondents who were both purposively and randomly selected. Data collection in this study was done using questionnaires and interviews. Findings of the study revealed a positive (.894), but statistically significant relationship between staff training and employee performance. The Pearson correlation of 0.928** revealed a positive but statistically significant relationship between career advancement and employee performance meaning that career advancement based on competencies of staff, provision of scholarship to staff to upgrade their knowledge and skills, having career progression plan guided on equity and merit and career progression guidelines which stipulates conditions for promotion are likely to bring about better employee performance geared towards timely achievement of town Council targets. The findings indicated a Pearson correlation of .0.961** which showed a positive but statistically significant relationship between career planning prospects and employee performance meaning that have personal career plan, providing career advisory services, having career development plan and internal and external programs that develop staff as well as self-assessment tools would result into better employee performance. The study concluded that staff training had positive significant relationship with employee performance in Kanungu District Local Government. The study concludes that career advancement has a positive significant influence on employees’ performance in Kanungu District Local Government. Career progression among the Town Councils was guided by specific criteria, career advancement in the Town Council based on competencies of staff and having a well-structured progression plan guided on equity and merit would improve on employees’ performance. The study concludes that career planning has a positive significant influence on employees’ performance.. The study recommended that the Town Councils should regularly assess the training needs of staff before undertaking any training. To improve the performance of staff in The Town Councils, career advancement should be based on competencies of staff, equity and merit and more scholarships should be awarded to staff to enable them advance career-wise. The Town Councils in Kanungu District Local Government should provide adequate career advisory services to its staff as well as have adequate and proper career development plan for its staff to improve on their overall performance.